The Influence of Tourism Activities on Tourism Decisions in The New Normal Era - Lusia, Erma; Kusumawardhana, Indra; Ikhsan, Ridho Bramulya (E-Journal of Tourism; Volume 11 Number 1 (March 2024)DO - 10.24922/eot.v11i1.108600, 2024)
After surviving the covid-19 epidemic, civilization must eventually adjust to a new normal. Currently, certain situations are unpredictable and cannot be anticipated or projected based on previous historical data. After enduring the lengthy quarantine and the tremendous mental stress brought on by the complicated circumstances, the priority for most individuals is to take vacations. Traveling to various locations that provide a variety of holiday experiences becomes a viable option to selecting. What attribute of a destination has become more important to individuals when they decide to travel? This study investigates the significance of destination attributes to travel decisions in the new normal. In this study, the spearman rank correlation is employed to analyse data collected randomly from 150 respondents. The study's results indicate that activity has significant relationship to travel decision. The findings of this research will aid the tourism sector in developing strategies for visitor-oriented activities. Another critical advantage is recognizing that customer behaviour directly impacts a company's long-term success.